Incomplete Information Bargaining with Applications to Mergers, Investment, and Vertical Integration - Loertscher, Simon; Marx, Leslie M. (American Economic Review, 2022)
We provide an incomplete information bargaining framework that captures the effects of differential bargaining power in markets with multiple buyers and multiple suppliers. The market is modeled as a mechanism that maximizes the expected weighted welfare of the firms, subject to the constraints of incentive compatibility, individual rationality, and no deficit. We show that, in this model, there is no basis for the presumption that vertical integration increases equally weighted social surplus, while it is possible that horizontal mergers that appropriately change bargaining weights increase social surplus. Moreover, efficient bargaining implies that in equilibrium noncontractible investments are efficient. (JEL C78, D82, D83, G34, K21, L22, L40)